The impact of bariatric surgery on hematological inflammatory parameters (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate hematological inflammatory parameters before and after bariatric surgery and investigate the effect of surgery on these parameters.Material and Methods: A total of 71 patients who underwent a Roux-en-Y gastric bypass (RYGBP) or a sleeve gastrectomy (SG) procedure were included in the study. The preoperative levels of the inflammatory parameters of C-reactive protein (CRP) and the white blood cell count (WBC), as well as the hematological inflammatory parameters of red blood cell distribution width (RDW), mean platelet volume (MPV), platelet distribution width (PDW), plateletcrit (PCT), and the neutrophil-to-lymphocyte ratio (NLR) were compared with the postoperative 6th and 12th month values.Results: Both the RYGBP and SG surgical techniques were used in this study. Significant reductions were seen in the postoperative 6th and 12th month values of CRP and WBC, which were used as an indicator of the severity of inflammation. Along with the decrease in BMI and the standard indicators of inflammation, there were also corresponding statistically significant changes in the levels of the more recently used hematological inflammatory markers of RDW, MPV, PDW, PCT, and NLR (p0.05).The statistical evaluation revealed a significant positive correlation between the serum WBC and CRP values and NLR measured at postoperative 6 th months. The postoperative 12 th month results indicated a significant positive correlation between the serum WBC and PCT values and also between the CRP and MPV values.Conclusion: Significant improvements were observed in previously elevated hematological inflammatory parameters in obese patients after bariatric surgery.
Keywords: Bariatric surgery; hematological inflammatory parameters; metabolic syndrome; obesity.